Growth attributes of malt barley (Hordeum vulgare) as influenced by fertility levels and liquid biofertilizers - ATHNERE, SONAL; CHAPLOT, P C; NAGRE, SURYAKANT; PATEL, RAJENDRA; S B, SALGAR; BOKADO, KANGUJAM; YADAV, PINKY; GARG, KAMAL (The Indian Journal of Agricultural Sciences, 2024)
The experiments were conducted during winter (rabi) seasons of 2020–21 and 2021–22 at Rajasthan College of Agriculture, Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan to study the effect of fertility levels and biofertilizers on malt barley (Hordeum vulgare L.). Factorial randomized block design (F-RBD) was used comprising 15 treatment combinations involved 3 fertility levels, viz. 50 N + 25 P2O5 + 15 K2O kg/ha; 60 N + 30 P2O5 + 20 K2O kg/ha; and 70 N + 40 P2O5 + 25 K2O kg/ha; alongside 5 liquid biofertilizers, viz. control; Azotobacter; Phosphorous solubilizing bacteria; Potassium mobilizing bacteria; and Azotobacter + Phosphorous solubilizing bacteria + Potassium mobilizing bacteria. The findings indicate that applying a fertilizer combination of 70 N + 40 P2O5 + 25 K2O kg/ha to malt barley crop significantly enhanced plant height at harvest (118.74 cm), dry- matter accumulation/m row at harvest (356.88 g), leaf area index (LAI) at 50 DAS (days after sowing) (1.69) and 75 DAS (2.87), number of total tillers (89.97) and growth efficiency values, substantially greater than other fertility levels. The findings demonstrated that inoculating seeds with a combination of liquid biofertilizers containing Azotobacter + Phosphorous solubilizing bacteria + Potassium mobilizing bacteria significantly improved growth parameters, viz. plant height at harvest (117.55 cm), dry-matter accumulation/m row at harvest (371.25 g), LAI at 50 DAS (1.68) and 75 DAS (2.96), number of total tillers (90.08) and growth efficiency values.